The Correlation of Effective Sentence and Paragraph Mastery with Narrative Writing Ability in Class V Students of SD Negeri 5 Marang South Pesisir District of West Pesisir in Academic Year 2018/2019 - Rusmidawati Rusmidawati; Surastina Surastina; Akhmad Sutiyono; Tri Riya Anggraini (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This research about the correlation of effective sentence and paragraph mastery with narrative writing ability in class v students of SDN 5 marang south pesisir district of west pesisir in academic year 2018/2019. This problem is deemed necessary to be investigated because students' mastery of effective sentences, paragraph mastery, and narrative writing skills is still low. The description and problem solving in the research are expected to be useful for students of SD Negeri 5 Marang, Pesisir Selatan District, Pesisir Barat Regency. This research uses the correlational method, namely to find out and describe the relationship between research variables. The goal is to make a description of the facts and characteristics of the population so that it can lead to a conclusion about the problem under study. The data collection technique used is the test technique. The test technique used to collect research data on vocabulary mastery and paragraph knowledge is by using multiple-choice objective tests. Meanwhile, to collect data on the ability to compose a narrative is a performance test. The results of the study show that: (1) there is a positive and significant relationship between effective sentence mastery and the ability to compose narratives, with a correlation coefficient of ry1 = 0.782, and a regression equation = 45,097 + 0.389 X1, (2) there is a positive and significant relationship between paragraph mastery and ability to compose narrative, with coefficient ry2 = 0.775 and regression equation = 49,583 + 0.347X2 and (3) there is a relationship between mastery of effective sentences and paragraphs with ability to compose narratives together with correlation coefficient ry 1.2 = 0.786 and regression equation = 18,831 + 0.391X1 + 0.349X2.